The Factors of Risk Management Effect at Slope Construction Site - Puspa Liza Ghazali; Dede Ansyari Guci; Eni Noreni Mohammad Zain; Hamidah Che Abdul x Hamid; Roslida Abdul Razak; Juliana Arifin; Sharifah Arni Syed Jaaffar; Norizan Remli (Husnayain Business Review, 2022)
Purpose – Products originated from cocoa are globally popular. Therefore there is an economic significance in developing the cocoa-based industry. Indonesia, as one of the countries having good quality cocoa specimens, should benefit from this commodity. However, the cocoa-based industry has not contributed much to Indonesia’s GDP. Thus, this paper seeks to understand Indonesia’s cocoa industry’s position within the cocoa industry’s global value chain and any difficulties that prevent the cocoa-based industry from flourishing in Indonesia. Approach - This paper drew from the literature on the cocoa industry in Indonesia and the cocoa global value chain. Findings - This research shows that Indonesia’s underdeveloped cocoa industry lacks an understanding of Indonesia’s cocoa value in the global value chains. This lack of understanding is prevalent in the Indonesian economic bureaucracy and local cocoa industrial actors’ perspective. Novelty – In the study of political economy, the optimization of economic benefits can be achieved through good synergy in political policies to support the achievement of maximum value added for a leading commodity in a country. When the synergy among the stakeholders is optimal, the implemented regulations can be adequately implemented.